Analysis of Procedures for Giving Home Ownership Credit (KPR) in Bank Tabungan Negara (Persero) Depok Branch - Helmina Br. Ginting (Kusuma Negara Business School, 2020)
This study is to analyze and understand how the procedure for providing Home Ownership Credit is carried out by the Bank Tabungan Negara, Depok Branch. The technique of collecting data is done by means of interviews, observations, documentation and from various other sources. This type of research is descriptive with a quantitative approach. The research was conducted at PT. Bank Tabungan Negara (Persero), Tbk. Depok branch. The data obtained are primary data, namely data obtained or collected directly based on the results of observations and interviews at PT. Bank Tabungan Negara (Persero), Tbk. Depok branch regarding the procedure for providing home ownership credit. Secondary data, namely data that has been available and processed to be used as a reference for research carried out such as the company's organizational structure. The data is obtained from books, information on the official website and brochures of the Bank Tabungan Negara. The steps of the analysis process in this study are, first, get the data needed from PT. Bank Tabungan Negara (Persero), Tbk. Depok branch. Second: Discuss and analyze these data, view and analyze the Procedure for Providing Housing Loans (KPR) at PT. Bank Tabungan Negara (Persero), Tbk. Depok branch. Third, the author draws conclusions on the discussion that has been done in the previous stage. Make conclusions, and provide suggestions if something is found that needs improvement. Based on the data analysis, it is concluded that the procedure for granting home ownership credit at PT. Bank Tabungan Negara (Persero), Tbk. The Depok branch is in accordance with the theory put forward by Kasmir (2012: 100). In calculating mortgage interest at PT. Bank Tabungan Negara (Persero), Tbk. Depok branch.